Translating affect, redeeming life. The case of the Italian queer transfeminist group ideadestroyingmuros. (2nd January 2019) - Baldo, Michela
ABSTRACT: This article looks at the role played by emotions and affect in activist translation, that is, translation understood as a tool for political change, by analyzing the Italian queer transfeminist group ideadestroyingmuros . Translation is conceived by this collective as a bodily act, a transformation of oneself in the act of migrating, as a way for, in the words of the collective, 'redeeming life, ' that is, improving living conditions. This transformation, for ideadestroyingmuros and other queer transfeminist groups, can indeed stem from the creation of more affective, supportive and cooperative conditions of living. The article will draw on the concepts of emotion and affect, as theorised by some scholars who dealt with them. Emotion and affect, with their emphasis on relationality and on the capacity to create action and to be affected by action, can demonstrate how translation impacts on translators, and how sociopolitical studies of translation can benefit from a view of ideological positioning as the outcome of a series of intricate emotional and affective journeys.